ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHINILAI TUKAR RUPIAH TERHADAP DOLLAR AMERIKA SERIKAT DENGAN PENDEKATAN NERACA PEMBAYARAN (PENDEKATAN ENGLE GRANGER-ERROR CORRECTION MODEL) - Setyowati, Eni; Soepatini, Soepatini (Universitas Muhammdaiyah Surakarta, 2004)
The equilibrium exchange rate will change along with the change of demand and supply. Factors causing the change of demand and supply curve among others are the amount of money supply, relative gross domestic product (GDP) ,the level of relative interest rate, and relative priceOne of the ways to analyze the influence of short term and long term is by developing the dynamic model. In this research, the analysis of dynamic model was conducted with Engel-Granger Error Correction Model approach which was developed by Engel-Granger (1987) based on Granger Representation Theorem.The ECM was known that long term exchange rate is influenced by the number of money supply and relative price. The variable which influence short-therm exchenge rate are the ammount of Gross Domestic Product, and interest rate.